Extended Wear Hydrophilic Lenses: And Insight into Clinical In-Office Patient Management - Mulhall, Tom (Canadian Journal of Optometry, 2021)
The use of soft contact lenses for extended wear can provide a beneficial and convenient therapy for patients where spectacles and/or daily wear contact lenses are contraindicated.